Description of a new species of Borneola MohamedSaid from Borneo with notes on their larvae (coleoptera:chrysomelidae: galerucinae. - Haruo Takizawa , (Pusat Sistematik Serangga ,UKM, 2011)
A new species of the genus Borneola MohamedSaid, B.mohamedsaidi, n.sp, was described from Sabah Malaysia. Larvae of B. hijau Mohamedsaid and another undetermined species of the genus were also described. Based on larval and adult characters it was concluded that the genus belongs to the section agelasticites of the subfamily Galerucinae